The Role of the Merah Putih Village Cooperative in Improving Community Welfare in Pondok Petir, Depok - Ratna Kartika Sari; Dewi Retno Budiastuti; Moch Syafii (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the role of the Merah Putih Village Cooperative (KDMP) in enhancing community welfare in Pondok Petir, Depok, West Java. A qualitative method was employed to gain an in-depth understanding of the cooperative's functions and its socio-economic impact on the local community. Data were collected through interviews, observations, and document analysis, with findings interpreted through the lenses of classical utilitarian welfare theory, neoclassical welfare theory, and the new contractarian approach. The results indicate that KDMP Pondok Petir, with 147 active members, supplies essential commodities—such as rice, eggs, cooking oil, and mineral water—at prices below market rates. Sourcing rice directly from farmers in Cianjur shortens the supply chain, reduces intermediary margins, and creates dual benefits: affordable prices for consumers and improved market access for producers. Lower prices reduce household food expenditures, freeing up disposable income for education, healthcare, and savings; this enhances consumer utility and purchasing power, particularly amidst local inflation of approximately 3% per year in Depok. The study concludes that KDMP has positively contributed to community welfare by lowering food costs, improving market access for farmers, and strengthening public trust in cooperative institutions. However, the cooperative currently faces limitations regarding commodity variety and remains reliant on manual bookkeeping. Strengthening institutional capacity, digitizing financial administration, and diversifying business activities are recommended to maximize KDMP's potential for fostering sustainable welfare improvements.